Kualitas Petis Daging dengan Sumber Pati Berbeda - Fajar Firdaus; Agus Susilo; Masdiana Chendrakasih Padaga (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2016)
The aimed of this research was to determine meat paste quality from different starch source, toward the physical, chemical and organoleptic properties. The meat paste was evaluated for starch content, protein content, viscosity and organoleptic. The experiment design used was Complete Randomize Nested. Meat broth was supplemented with tapioca starch, gaplek starch, and sweet potato starch in different concentration. Analized amino acid profiles to the best result from the experiment. The different starch source with different concentration gave significantly different to the quality of the meat paste based on starch properties content, viscosity, and gave highly significant effect on color, flavor, and taste. The best quality meat paste was obtained from sweet potato starch.